Investigating the Influencing Factors of Online Purchase in E-commerce Platforms - Ong, Yee Ching; Shamsuddin, Alina (Research in Management of Technology and Business, 2025)
E-commerce platforms development has changed the way consumer making purchase from traditional shopping into online shopping. The convenient of online shopping has made e-commerce become dominant, leading to increase in online purchases. However, there is a gap in understanding the specific factors that influence consumers’ online purchase intention on e-commerce platforms among different states in Malaysia. The complaints from consumers about the inconvenience of traditional shopping are also rising. Hence, this study is to determine the relationship between influencing factors which are perceived usefulness, perceived ease of use, perceived risk, perceived benefits with consumers’ online purchase intention in e-commerce. The simple random sampling method was applied in this study to make sure the validity and reliability of the findings. A quantitative method was used to collect the data from 384 e-commerce platforms users in Johor using questionnaires with a response rate of 74.22%. The data collected were analysed using descriptive and correlation analysis. The results indicated that influencing factors related to are perceived usefulness, perceived ease of use, perceived risk, perceived benefits have significant relationship with online purchase intention. Therefore, the e-commerce business should consider these factors while designing strategies and enhancing platform features to effectively meet consumers’ needs and drive online purchase intentions.